Gorham's disappearing bone disease: a rare cause of extensive bone destruction - Suppiah, Subapriya; Muridan, Roziah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2016)
Osteolytic disease of the bones have a myriad range of aetiology. One rare cause is Gorham’s disease or disappearing bone disease. This disease is a diagnosis by exclusion using correlation made with clinical presentation, radiological findings and histopathological confirmation. Although many different therapies have been advocated, none have been successful in fully controlling this disease. We present a case that was detected in a Chinese lady using diagnostic imaging, confirmed with computed tomography guided biopsy and successfully treated with joint reconstruction using endoprosthesis.